Age and gender differences in vertebral bone marrow adipose tissue and bone mineral density, based on MRI and quantitative CT. Issue 159 (February 2023) - Yu, Aihong; Huang, Mingqian; Wang, Ling; Zhang, Yong; Li, Kai; Lou, Luxin; Liang, Wei; Blake, Glen M.; Deng, Wei; Cheng, Xiaoguang
Abstract: Purpose: To investigate the age and gender differences in vertebral bone marrow adipose tissue (BMAT) and volumetric bone mineral density (vBMD). Method: A total of 427 healthy adults, including 175 males (41 %) and 252 females (59 %) with an age range of 21–82 years, underwent MRI and quantitative CT examinations of the lumbar spine (L2-L4), and the corresponding BMAT and vBMD values were measured. The age-related progressions of BMAT and vBMD in men and women were evaluated and compared. Results: In males, vertebral BMAT rose gradually throughout life, while in females, BMAT increased sharply between 41 and 60 years of age. In participants aged < 40 years, BMAT was greater in males compared to females (p ≤ 0.01), while after the age of 60, BMAT was higher in females (p < 0.05). In males, vBMD decreased gradually with age, while in females, there was a sharp decrease in vBMD after the age of 40 years. At age of 31–40 years, vBMD was higher in females (P < 0.002), while at age > 60 years, vBMD was higher in males (61–70 years, P < 0.01; > 70 years, P = 0.02). Conclusions: We found significant age and gender differences in lumbar BMAT and vBMD. These findings will help to improve our understanding of the interaction between bone marrow fat content and bone mineral density in the ageing process.